British Athletics
UK Athletics - the governing body for the sport of athletics in Great Britain with its headquarters based in Birmingham. On the structure and aims of UK Athletics, which has been formed following the well-chronicled financial demise of BAF ("British Athletic Federation"), as a new body for athletics in GB.